Assessment of serum and salivary oxidant and total antioxidant status of patients with recurrent aphthous stomatitis in a sample of Basrah city - Al-Essa, Hussein S; Zaidan, Taghreed F (Journal of Baghdad College of Dentistry, 2013)
Background: Recurrent Aphthous Stomatitis (RAS) is the most common painful oral mucosal disease, affecting approximately 20% of the population. RAS presents with a wide spectrum of severity ranging from a minor nuisance to complete debility. Many of factors thought to have been involved in its etiology; that might have at the same time a direct or indirect impact upon oxidant/antioxidant system and trigger free radicals production. The aim of this study was to determine the possible association of oxidant/total antioxidant status and recurrent aphthous stomatitis (RAS).Subjects, materials and methods: The study consisted of thirty patients with recurrent aphthous stomatitis and thirty healthy controls from which saliva and blood samples were collected. Malondialdehyde as an oxidative stress biomarker and total antioxidant status were measured in serum and saliva.Results: Malondialdehyde in serum and saliva was significantly higher in recurrent aphthous stomatitis patients in comparison to healthy controls (P0.05).Conclusions: The changes in the oxidative stress in biological systems can be induced by the consumption of antioxidants and/or by an overload of oxidant species, so the antioxidant defense system become deficient that may be important in the inflammatory reactions observed in recurrent aphthous stomatitis.